A Survey on User Experience of Blockchain Transactions: Security and Adaptability Issues - Handayani, Indri; Apriani, Desy; Mulyati, Mulyati; Aprila Yusuf, Natasya; Rahmania Az Zahra, Achani (IAIC Bangun Bangsa, 2023)
Blockchain technology has become a major focus of digital change in recent years. Initially known as the infrastructure that supports digital currencies, blockchain now has enormous potential in improving user experience across a wide range of sectors. The application of this technology is capable of addressing a variety of issues that exist in the industry, including issues of trust, transparency, security, and reliability of data processing. In this paper, we will explore various applications of blockchain technology that aim to improve user experience in transactions. We will explain the concept of blockchain technology, analyze its advantages and disadvantages, and identify factors that affect its success or obstacles that may arise during implementation. By understanding the potential of blockchain technology and its applications that can improve user experience in transactions, we can pave the way for further progress in providing more secure, efficient, and transparent solutions for transaction activities in the future. The methodology employed in this study involves conducting a survey through online questionnaires that were distributed to individuals knowledgeable about the concept of blockchain technology with a total sample size of 96 people. The analysis approach used is Smart PLS. Thus, this research is expected to provide a deeper insight into the application of blockchain technology to improve user experience in transactions.